2015
DOI: 10.1097/mop.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant polycystic kidney disease in children

Abstract: Purpose of review Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary renal disease, affecting one in 500 individuals. The cardinal manifestation of ADPKD is progressive cystic dilatation of renal tubules with kidney enlargement and progression to end-stage renal disease in approximately half of cases by 60 years of age. Although previously considered a condition of adults, it is clear that children and young adults are subject to the complications of ADPKD. Recent findings It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 96 publications
1
39
0
2
Order By: Relevance
“…This study found that ACEi treatment in normotensive (BP 75 to 95th percentile) or borderline hypertensive (BP ≤75 percentile) children with ADPKD could prevent or significantly reduce the development of LVH and the decline in renal function [71]. These benefits occurred in the absence of any positive effect on kidney volume [58,68,71]. Surprisingly, these secondary benefits of ACEi did not apply to hypertensive ADPKD children [71].…”
Section: Clinical Manifestationsmentioning
confidence: 79%
See 3 more Smart Citations
“…This study found that ACEi treatment in normotensive (BP 75 to 95th percentile) or borderline hypertensive (BP ≤75 percentile) children with ADPKD could prevent or significantly reduce the development of LVH and the decline in renal function [71]. These benefits occurred in the absence of any positive effect on kidney volume [58,68,71]. Surprisingly, these secondary benefits of ACEi did not apply to hypertensive ADPKD children [71].…”
Section: Clinical Manifestationsmentioning
confidence: 79%
“…Renal manifestations in children with ADPKD are comparable to renal manifestations in affected adults [58]. In adult ADPKD, creatinine levels rise only in the advance stages of disease after non-cystic parenchyma has been permanently destroyed by expanding renal cysts.…”
Section: Clinical Manifestationsmentioning
confidence: 81%
See 2 more Smart Citations
“…Early intervention may have the greatest effect on the course of the disease by minimizing long-term complications [26,27]. Given that there is great heterogeneity in ADPKD progression, even within a given family [10], early intervention may be of particular significance to patients at the highest risk of progression, which notably includes VEO patients.…”
Section: Discussionmentioning
confidence: 99%